A dual-band microstrip patch antenna for 2.45/5-GHz WLAN applications - CIRIK ACIKAYA, FUNDA (ELSEVIER GMBH, 2021)
A microstrip transmit patch antenna with harmonics suppression property has been designed for the 2.45/5-GHz WLAN bands. Patch antennas usually have narrow bandwidths and the 5-GHz WLAN band extends from 5.15 to 5.8 GHz, which makes the design challenging. The proposed antenna has two cuts at two of its edges in order to achieve a wide bandwidth for the 5-GHz WLAN band. In addition, a microstrip matching circuit has been implemented to improve the 2.45-GHz low-band response. A low-cost and easily available FR4 substrate has been used for the design and fabrication of the antenna. The presented antenna offers harmonic supression at 4.9 and 7.35 GHz to reduce interference with other receivers. Design process involved extensive electromagnetic simulations. Measured design parameters of the proposed antenna are in good agreement with the simulations.
Keywords: Microstrip patch antennas; WLAN antennas; Harmonics suppression; Antenna measurements; HARMONIC SUPPRESSION; UWB ANTENNA; MODE; DESIGN